Effectiveness over time of a primary series of the original monovalent COVID-19 vaccines in adults in the United States - J. Bradley Layton; Patricia C. Lloyd; Lauren S. Peetluk; Yixin Jiao; Djeneba Audrey Djibo; Joann F. Gruber; Jie Deng; Christine Bui; An-Chi Lo; Rachel P. Ogilvie; Ron Parambi; Michael Miller; et al. (PLoS ONE, 2025)
With data from 2 US claims databases (Optum, CVS Health) supplemented with Immunization Information System COVID-19 vaccine records, we evaluated overall and time-specific vaccine effectiveness (VE) of an initial primary series for 3 monovalent COVID-19 vaccines—BNT162b2, mRNA-1273, and JNJ-7836735—in adults (18-64 years). Vaccinated individuals were matched to unvaccinated comparators, and we estimated VE against any medically diagnosed COVID-19 and hospital/emergency department (ED)-diagnosed COVID-19. Additionally, we estimated VE by era of predominant variants, in subgroups, and compared across vaccine brands. The cohorts consisted of 341,097 (Optum) and 1,151,775 (CVS Health) matched pairs for BNT162b2; 201,604 (Optum) and 651,545 (CVS Health) for mRNA-1273; and 49,285 (Optum) and 149,813 (CVS Health) for JNJ-7836735. The study period began 11 December 2020 (date of first COVID-19 vaccine availability in the US) and ended 15 January 2022 in Optum and 31 March 2022 in CVS Health. Summary VE estimates from meta-analysis against hospital/ED-diagnosed COVID-19 were: BNT162b2, 77% (95% CI, 76%-78%); mRNA-1273, 84% (95% CI, 83%-85%), JNJ-7836735 66% (95% CI, 63%-68%). VE estimates were higher for hospital/ED-diagnosed COVID-19 than for medically diagnosed COVID-19, and VE estimates were highest in adults receiving mRNA-1273 for both outcomes. VE was sustained for approximately 7 months for medically diagnosed and up to 9 months for hospital/ED-diagnosed COVID-19. VE differed by brand and variant era. Ongoing real-world surveillance of COVID-19 vaccines using robust data sources and methodology is needed as new variants and recommendations for updated vaccines have evolved.